Review of "Emerging Markets Resilience and Growth Amid Global Turmoil by M. Ayhan Kose and Eswar S. Prasad" - C. Bora Durdu (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
Emerging Markets Resilience and Growth amid Global Turmoil provides an excellent contribution to the literature. The book covers a variety of important topics on emerging market economies and offers invaluable information for a wide range of audience; from academics to policy makers as well as anyone interested in learning about these countries. The vast amount of information provided in the book is, then, used to shed light on an important question: What explains the resilience of emerging market economies observed during and in the aftermath of the global financial crisis? This review presents a brief summary of the book and a discussion about its implications for future research.
Keywords: 330; Wirtschaftswachstum; Internationale Wirtschaft; Globalisierung; Konjunkturzusammenhang; Finanzkrise; Weltwirtschaftsordnung; Internationaler Finanzmarkt; Schwellenländer